2005
DOI: 10.1021/ol050117y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Enamides via Palladium-Catalyzed Amidation of Enol Tosylates

Abstract: [reaction: see text] A Pd-catalyzed coupling of enol tosylates and amides has been developed. Ligand screening revealed dipf as the most general ligand for this transformation. A variety of enol tosylates were coupled to an array of enamides in 58-97% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(91 citation statements)
references
References 19 publications
1
89
0
1
Order By: Relevance
“…[134] Chemists at Merck have shown that to couple vinyl triflates [135] and vinyl tosylates [136] with an activating substituent at the β position with amides the best systems are provided by the chelating ligands Xantphos and dipf (1,1′-bis(di-iso-propylphosphino)ferrocene) respectively. When Willis came to examine the coupling of unactivated vinyl triflates and tosylates, however, ligand 6 proved to be optimal (Scheme 4).…”
Section: Synthesis Of Imines Enamines and Enamidesmentioning
confidence: 99%
“…[134] Chemists at Merck have shown that to couple vinyl triflates [135] and vinyl tosylates [136] with an activating substituent at the β position with amides the best systems are provided by the chelating ligands Xantphos and dipf (1,1′-bis(di-iso-propylphosphino)ferrocene) respectively. When Willis came to examine the coupling of unactivated vinyl triflates and tosylates, however, ligand 6 proved to be optimal (Scheme 4).…”
Section: Synthesis Of Imines Enamines and Enamidesmentioning
confidence: 99%
“…Deprotection of the alcohol (TBAF, THF) led to ynamide 6, which underwent stereoselective hydroalumination with Red-Al to provide the (E)-3-(N-tosylamino)allylic alcohol 3 a (68 %, two steps from 5). Alternatively, ynamide 5 was treated with an excess of the titanium reagent [h 2 -(propene)]TiA C H T U N G T R E N N U N G (OiPr) 2 , [6h,i] followed by hydrolysis to provide enamide 7 and subsequent cleavage of the silyl ether (TBAF) afforded the isomeric Z allylic alcohol 3' a (59 %, two steps from 5) (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…The low and abnormal diastereoselectivity observed in the Ireland-Claisen rearrangement of glycolate 22 led us to explore the alternative route towards 1,2-amino alcohols E relying on the use of a [2,3]-Wittig rearrangement.…”
Section: Sulfonamidementioning
confidence: 99%
See 2 more Smart Citations